Developing a relational playbook for cardiology teams to cultivate supportive learning environments, enhance clinician well‐being, and veteran care - Heather M. Gilmartin; Brigid Connelly; Edward Hess; Candice Mueller; Mary E. Plomondon; Stephen W. Waldo; Catherine Battaglia (Wiley, 2024)
Abstract Introduction Despite the Veterans Health Administration (VA) efforts to become a learning health system (LHS) and high‐reliability organization (HRO), interventions to build supportive learning environments within teams are not reliably implemented, contributing to high levels of burnout, turnover, and variation in care. Supportive learning environments build capabilities for teaching and learning, empower teams to safely trial and adapt new things, and adopt highly reliable work practices (eg, debriefs). Innovative approaches to create supportive learning environments are needed to advance LHS and HRO theory and research into practice. Methods To guide the identification of evidence‐based interventions that cultivate supportive learning environments, the authors used a longitudinal, mixed‐methods design and LHS and HRO frameworks. We partnered with the 81 VA cardiac catheterization laboratories and conducted surveys, interviews, and literature reviews that informed a Relational Playbook for Cardiology Teams. Results The Relational Playbook resources and 50 evidence‐based interventions are organized into five LHS and HRO‐guided chapters: Create a positive culture, teamwork, leading teams, joy in work, communication, and high reliability. The interventions are designed for managers to integrate into existing meetings or trainings to cultivate supportive learning environments. Conclusions LHS and HRO frameworks describe how organizations can continually learn and deliver nearly error‐free services. The Playbook resources and interventions translate LHS and HRO frameworks for real‐world implementation by healthcare managers. This work will cultivate supportive learning environments, employee well‐being, and Veteran safety while providing insights into LHS and HRO theory, research, and practice.